Secure Data Deduplication by Using Convergent Key Technique - B.Tirapathi Reddy, Mr; K.V. Padmasree, Ms; K KrishnaKanth, Mr; Dushyanth KumarReddy, Mr (International Journal of Engineering and Technology, 2018)
Data de-duplication is the significant system used for removal the repetitive copy of information and broadly use in cloud storage to decrease and upload bandwidth. Our main motto be toward accomplish safe de-duplication within cloud. Convergent encryption has been utilized for safe de-duplication, complication is having colossal number of convergent keys. We will be utilizing base line approach in which each of the user have their own masterkey for encrypting their convergent keys also send them to cloud. This approach produces huge amount of keys with increment in amount of user and it needs help of user to look after master keys. At ending we will have De-key in which users need not deal with the key on their individual except steadily circulate convergent key among many servers.Â Â